2006
DOI: 10.1176/appi.ps.57.10.1452
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Substance Abuse Outcomes Module

Abstract: The SAOM appears to be a reasonably reliable and valid self-report instrument when used to monitor substance abuse treatment among patients with a primary substance use diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 0 publications
2
76
0
Order By: Relevance
“…They also were asked to record the number of days that they used each of the following: marijuana, cocaine or crack, stimulants (prescribed and nonprescribed), opiates (prescribed and nonprescribed), sedatives (prescribed and nonprescribed), and heroin. The SAOM has demonstrated strong psychometric properties, including high internal consistency (Chermack et al, 2000), test-retest reliability (Smith et al, 2006), and concurrent validity with widely used measures of alcohol and drug problem severity measures such as the Addiction Severity Index (McLellan et al, 1992). Although the SAOM asks questions about both prescription use and illicit substance use, the present study focused solely on the illicit use of these substances, whether prescribed or not.…”
Section: Methodsmentioning
confidence: 99%
“…They also were asked to record the number of days that they used each of the following: marijuana, cocaine or crack, stimulants (prescribed and nonprescribed), opiates (prescribed and nonprescribed), sedatives (prescribed and nonprescribed), and heroin. The SAOM has demonstrated strong psychometric properties, including high internal consistency (Chermack et al, 2000), test-retest reliability (Smith et al, 2006), and concurrent validity with widely used measures of alcohol and drug problem severity measures such as the Addiction Severity Index (McLellan et al, 1992). Although the SAOM asks questions about both prescription use and illicit substance use, the present study focused solely on the illicit use of these substances, whether prescribed or not.…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol and Drug Consumption: Participants were asked about their drug and alcohol use in the 28 days before entering treatment using questions from the University of Arkansas Substance Abuse Outcomes Module (SAOM; Smith et al, 2006). Four questions were asked relating to alcohol: the number of days of alcohol use; average number of drinks consumed each drinking day; maximum number of drinks consumed; and the number of days involving binges (more than five drinks consumed).…”
Section: Proximal Risk Factorsmentioning
confidence: 99%
“…Participants were also asked to record the number of days that they used each of the following: marijuana; cocaine or crack, stimulants (prescribed and non-prescribed); opiates (prescribed and non-prescribed); sedatives (prescribed and non-prescribed); heroin; PCP; other hallucinogens; inhalants; anabolic steroids; and tobacco. The SAOM has undergone extensive reliability and validity examinations (Smith et al, 2006) and has demonstrated strong psychometric properties including high internal consistency (Chermack et al, 2000), test-retest reliability (Smith et al, 2006) and concurrent validity with widely used substance abuse measures such as the Addiction Severity Index (McLellan et al, 1992). The following substance use frequency variables were included in the analyses: heavy drinking days, marijuana use, cocaine use, heroin use, illicit opiate and sedative use, and illicit stimulant use.…”
Section: Proximal Risk Factorsmentioning
confidence: 99%
“…55 Primary care service utilization was assessed by modified questions from the Substance Abuse Outcomes Module. 68 Criminal Justice-Current legal status (i.e., on probation/parole) was assessed using a "yes" or "no" item, from the Addiction Severity Index. 69 Retaliation-The assault-injured group reported whether or not they thought that the conflict that brought them to the ED was over (i.e., "Do you think that the conflict that caused this incident is over?…”
Section: Methodsmentioning
confidence: 99%